Historical estimates of national accounts magnitudes in Greece: 1830-1939 - Κωστελένος Γεώργιος Κ. (SPOUDAI Journal of Economics and Business, 2003)
The study of long run economic development is facilitated immensely by the existence of relevant data. In this context, long run national accounts magnitudes are probably the most important. This has been realized since the early 1950s by economists of the stature of Kuznets, Friedman and North and relevant time series have been estimated, originally for countries like the U.S.A. and Great Britain and subsequently for other developed and less developed countries. In Greece, however, the first relevant attempt undertaken in recent years appeared in 1995, previous estimates, dated in the early 1950s and before, having been "forgotten" in time. In this article, these earlier estimates are reviewed JEL Classification: N13-14